Is Telehealth Right for Your Practice and Your Patients With Asthma?. (March 2017) - Brown, Wendy; Schmitz, Tara; Scott, David M; Friesner, Daniel
Introduction: Telehealth services are becoming increasingly used to provide care to patients living in rural areas. Little is known about the patient satisfaction with the provision of these services. Methods: A prospective cohort pilot study was developed to evaluate the use of telehealth for the delivery of asthma education services in the rural, medically underserved community of Oakes, North Dakota. A certified asthma educator used real-time, audio-visual telehealth technology to meet with patients the local community pharmacy. Patients met with the educator monthly for the first three months of the study, and once every three months thereafter. Patient satisfaction was measured using a five item survey. Results: Eighteen patients completed the study (90 percent completion rate). Patient satisfaction scores were relatively high, typically between 4 and 5 on a 5-point scale. Conclusions: Participants in a rural, medically underserved community found the community pharmacy location and the telehealth technology a convenient means to access a specialty provider for asthma education.